2017
DOI: 10.1371/journal.pone.0177993
|View full text |Cite
|
Sign up to set email alerts
|

Different adaptation strategies of two citrus scion/rootstock combinations in response to drought stress

Abstract: Scion/rootstock interaction is important for plant development and for breeding programs. In this context, polyploid rootstocks presented several advantages, mainly in relation to biotic and abiotic stresses. Here we analyzed the response to drought of two different scion/rootstock combinations presenting different polyploidy: the diploid (2x) and autotetraploid (4x) Rangpur lime (Citrus limonia, Osbeck) rootstocks grafted with 2x Valencia Delta sweet orange (Citrus sinensis) scions, named V/2xRL and V/4xRL, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…The tetraploid Carrizo citrange appears to be less sensitive to boron excess than the corresponding diploid [24]. Transcriptome studies revealed constitutive overexpression of genes involved in stress response in tetraploid citrus compared to their diploid parents [18,19,25].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The tetraploid Carrizo citrange appears to be less sensitive to boron excess than the corresponding diploid [24]. Transcriptome studies revealed constitutive overexpression of genes involved in stress response in tetraploid citrus compared to their diploid parents [18,19,25].…”
Section: Introductionmentioning
confidence: 95%
“…Under salinity stress or water deficit, tetraploid seedlings were shown to be more tolerant than their parental diploid counterparts [12][13][14][15][16][17]. Increased tolerance was also observed when rootstock was grafted [18][19][20]. Better tolerance to cold was reported in clementine trees grafted onto tetraploid Carrizo citrange [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the citrus industry, the use of suitable rootstocks plays a very important role in commercial citrus production. The rootstock has a significant impact on plant vigor, yield, fruit quality, and disease resistance 24 27 . Additionally, the rootstock can also affect the metabolome of citrus fruit juice, which determines the flavor and nutrition of the fruit 3 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In citrus, polyploidy has been described to improve adaptation to different stresses and resilience ( Mouhaya et al, 2010 ; Podda et al, 2013 ; Allario et al, 2013 ; Tan et al, 2015 ; Tan et al, 2017 ; Dutra de Souza et al, 2017 ; Oliveira et al, 2017 ; Oustric et al, 2017 , 2018 ), and several teams worldwide have been developing rootstock breeding at the tetraploid level ( Grosser and Chandler, 2000 ; Grosser et al, 2000 , 2015 ; Ollitrault et al, 2000 , 2007 ; Guo et al, 2007 ; Grosser and Gmitter, 2010 ; Dambier et al, 2011 ; Guerra et al, 2016 ). Many of these programs focus on combinations of Citrus species with Poncirus , a related genus.…”
Section: Introductionmentioning
confidence: 99%